Simulation of ILC feedback BPM signals in an intense background environment - Hartin, A; Burrows, P; Christian, G; Clarke, C; Constance, B; Khah, H; Perry, C; Swinson, C; Arnold, R; Molloy, S; Smith, S; White, G; et al. (2007)
Experiment T-488 at SLAC, End Station A recorded distorted BPM voltage signals and an accurate simulation of these signals was performed. Geant simulations provided the energy and momentum spectrum of the incident spray and secondary emissions, and a method via image charges was used to convert particle momenta and number density into BPM stripline currents. Good agreement was achieved between simulated and measured signals. Further simulation of experiment T-488 with incident beam on axis and impinging on a thin radiator predicted minimal impact due to secondary emission. By extension to worst case conditions expected at the ILC, simulations showed that background hits on BPM striplines would have a negligible impact on the accuracy of beam position measurements and hence the operation of the FONT feedback system.